Pengaruh Aglomerasi Industri Terhadap Kualitas Lingkungan di Pulau Sumatera - Bima, Bima Prasetya Kumara (Salam (Islamic Economics Journal), 2025)
This study aims to analyze the effects of economic activity and industrial agglomeration on environmental quality on the island of Sumatra. A quantitative approach is employed using provincial panel data across Sumatra over a specified observation period. The estimation method applied is panel data regression with the Fixed Effect Model (FEM), selected based on the results of model selection tests. The independent variables in this study include gross regional domestic product of the industrial sector and the level of industrial agglomeration, while environmental quality is used as the dependent variable. The estimation results indicate that industrial economic activity has a significant effect on environmental quality, whereas industrial agglomeration does not show a significant effect. These findings suggest that increased economic activity has important implications for environmental conditions, but the spatial concentration of industry does not necessarily have a direct impact on environmental quality. In addition, the results of classical assumption tests indicate that the model is free from multicollinearity and heteroskedasticity problems, ensuring that the estimated results are consistent. This study is expected to provide empirical contributions to the formulation of more sustainable industrial development policies at the regional level.